PENGARUH PARAMETER PROSES 3D PRINTING MENGGUNAKAN FILAMEN ESUN PLA +, MENGGUNAKAN METODE TAGUCHI - Berlian Adinata Intani Adinata; Hasdiansah Hasdiansah; Zaldy Sirwansyah Suzen (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2021)
The presence of 3D printing answers all the needs of designers to digitally print a design into a product. 3D printing is the process of making an object by placing a thin layer sequentially formed according to the desired shape. This research examines the effect of the 3D Printing Process Using ESUN PLA+ Filament, Using the Taguchi Method. The methods used in this research are: Experiment, at this stage the printing process will be carried out based on the process parameters that will be tested with the Taguchi L25 rule. This study aims to determine the results of the roughness test based on the parameters in the 3D Printing process. In the test results on the side of the specimen, of the 6 factors tested (layer thickness, printing speed, nozzle temperature, Type Infill, flowrate & cooling speed) with 5 levels for each factor, the effect of these factors is not significant. In the test results on the top of the specimen, of the 6 tested factors (layer thickness, printing speed, nozzle temperature, Type Infill, flowrate & cooling speed) with 5 levels for each factor where there is an influence of roughness on these factors, it turns out that the factor (layer thickness, Type Infill & Cooling Speed) have the greatest influence on the roughness of the ESUN PLA+ material.